Information systems and technology sourcing strategies of e‐Retailers for value chain enablement. Issue 6 (27th July 2013) - Tsai, Juliana Y.; Raghu, T.S.; Shao, Benjamin B.M.
Abstract: In the e‐Retail industry, a well‐designed IT infrastructure is essential in creating a tightly integrated value chain and delivering high quality service. With intense competition for market share and profits, information systems and technology (IST) sourcing decisions are becoming increasingly important to e‐Retail firms to support continued growth and market responsiveness. Drawing on the contingency theory, we examine organizational and environmental factors that influence an e‐Retailer's IST sourcing strategy of make versus buy in enabling its value chain activities, and we also look at firm‐level performance impacts of IST sourcing decisions that involve bundling across value chain activities. We test the proposed model and hypotheses using a panel data set of 307 firms over the period of 2006–2010. The results show that firms that make transformative IT investments tend to source a smaller portion of IST for their e‐Retail value chain activities than firms that pursue automate or informate as their strategic role for IT investment. Capabilities are positively associated with IST sourcing. Firms experienced in e‐Retail are more likely to build rather than buy their IST. In addition, we find mimicking behavior for IST sourcing among firms in the same merchandizer category. We find that IT strategic role is strongly associated with growth metric, whereas sourcing decisions predominantly impact operational performance measures. There is partial evidence that alignment between IT strategic role and IST sourcing decisions results in better performance effects. Moreover, complementary IST sourcing of synergistic marketing and sales activities positively impacts Web sales and conversion rate, but the sourcing combination of logistics, operations, and sales activities is associated with lower Web sales and conversion rate.